A study on the correlation between work stressors and the coping styles of outpatients and emergency nurses in 29 pediatric specialty hospitals across China - Song, Nan; Wang, Chun-Li; Zhang, Lin-Qi; Wang, Xu-Mei (Frontiers in Psychology, 2022)
Objective: This study aimed to better understand the current situation involving work stressors and the coping styles of outpatient and emergency nurses in 29 pediatric specialty hospitals across China. The study analyzed this correlation to provide reference for the occupational stress management of pediatric nurses. Methods: From June to September 2020, 1,457 outpatient and emergency nurses in 29 pediatric specialty hospitals across China were selected as study participants, and a questionnaire survey was conducted using the Basic Information Questionnaire, the Chinese version of the Work Stressor Scale for Nurses, and the Simple Coping Style Scale. Results: The total scores of outpatient and emergency nurses in 29 pediatric specialty hospitals nationwide were (466.64 ± 218.05), which were lower than the national normative scores (P < 0.05). The stressors related to nurses’ expectations, family conflicts, the nature of nursing work, patient factors, and workload were lower compared with the national norm (P < 0.05). The positive coping style score on the Simple Coping Style Scale for pediatric outpatient nurses was (36.66 ± 6.16), and work stressors were positively associated with negative coping styles (P < 0.01). Multiple regression analysis showed that the influencing factors of work stressors among pediatric outpatient and emergency nurses correlated with the authorized size, age, working years of nurses, work department, and negative coping styles. Conclusion: Negative coping styles were present among pediatric outpatient and emergency nurses and were associated with work stressors. The influencing factors of stressors mainly correlated with the clinical establishment, age, years of employment as a nurse, work department, and negative coping styles.